Rumensin and drylot vs. pasture systems for early-weaned calves - Busby, W.D.; Corah, L.R.; McKee, M.; Fink, G.; Pope, Ronald V. (Kansas State University. Agricultural Experiment Station, 2011)
Seventy-six Polled Hereford and percentage Simmental calves were used to evaluate Rumensin and drylot vs. pasture systems by average daily gain of early-weaned (54 day old) calves. Rumensin was fed at 10 g/ton of feed for 28 days and 20 g/ton thereafter. The starter and standard creep rations were self-fed to both the drylot and pasture groups. Drylot calves outgained calves on pearl millet pasture 196 lbs to 140 lbs during the 76-day pasture trial. Rumensin decreased fecal samples containing coccidial oocytes and improved total gain 5.5% and feed efficiency 4.8%.
Keywords: Beef; Drylot vs. Pasture Systems; Early-weaned calves